PS-079 Implementation of proactive medicines reconciliation to reduce drug errors at admission. (24th March 2015) - Renet, S; Raymond, J; Bravo, P; Haddad, R; Bussone, G; Laquerriere, B; Fior, R; Rieutord, A; Curatolo, N
Abstract : Background: Medicines reconciliation (MR) is a critical step for reducing medicines errors (ME) at admission to hospital care. However, because of resource constraints it can be difficult to implement in hospital pharmacists' everyday practice. The Lean method is used to streamline and optimise processes considering all stakeholders and resources. Purpose: To redesign the medicines management process at admission to reduce MEs. Material and methods: A Lean approach review was conducted of the current medicines management process at admission (retroactive MR process) in order to define the new process (proactive MR), with all the stakeholders (clinicians, nurses, pharmacists, pharmacy technicians, head nurses). 5 activities were performed: mapping of the current process (retroactive MR process) measure of unintended medicines discrepancies (UMDs) at admission analysis of the collected data and root cause implementation design of a new improved process (proactive MR) implementation and measurement of the new process Only patients more than 65 years old and/or taking at least 3 medicines before admission were included. Results: 52 patients were initially included (75 years, 7.4 medicines/patient). 46% had at least 1 UMD (0.75 UMDs/patient) and 28.2% of UMDs had the potential to cause moderate to severe discomfort or clinical deterioration. After implementation of the new MR process, 50 patients were included (70 years, 6.9 medicines/patient). The percentage of patients with at least 1 UMD decreased to 12% (p < 0.01) (0.16 UMDs/patient) and 28.6% of UMDs had the potential to cause moderate to severe discomfort or clinical deterioration. Conclusion: Results demonstrate that proactive MR is effective in reducing ME on admissions orders and suggest that Lean is fully adapted to improve the medicines management process. Other studies are warranted to evaluate the impact of Lean on ME reduction. References and/or acknowledgements: No conflict of interest.